Perbedaan Kualitas Seksual pada Wanita Akseptor KB Hormonal dengan KB Non-Hormonal - Winda Nurmayani; Misroh Mulianingsih; Ni Ketut Ika Mustika Suarnaya (Poltekkes Kemenkes Surakarta, 2020)
Background: Sexual intercourse in the family is the peak of harmony, therefore both parties must be able to enjoy it together. Sex dissatisfaction can lead to differences of opinion, disputes and ultimately divorce. Hormonal contraception has side effects, one of which is an imbalance of the hormones estrogen and progesterone which can cause changes in sexual activity. Each type of family planning has its own side effects, but in most cases a decrease in sexual desire is a side effect that can be found in every use of the type of family planning. The purpose of this study was to determine differences in sexual quality in female hormonal and non-hormonal family planning acceptors.Methods: Descriptive analytic type of research with a comparative design using the Case Control approach, a sample of 68 Wus which is a hormonal and non-hormonal family planning acceptor. Simple Random Sampling sampling technique and observation sheet instrument and SQOL-F questionnaire. This research uses Chi Square data analysis.Results: Chi Square Continuity Corrections test results showed significant results P = 0.000 (P <0.1), meaning that P value 0.000 is smaller than 0.1 there are differences in sexual quality in female hormonal and non-hormonal KB acceptors.Conclusion: Most non-hormonal family planning acceptors have good sexual qualities while hormonal birth control acceptors mostly have moderate sexual quality.